"The Earth Gives Us So Much": Agroecology and Rural Women's Leadership in Uruguay. (June 2016) - Oliver, Beatriz
Abstract: Created by women farmers in the late 1980s, the Calmañana herb co‐operative is a significant figure in Uruguay's agroecology movement. Technical assistance grounded in participatory feminist and agroecological perspectives aided the group to organize and establish their production and marketing system. Rather than promote specialization, the process enhanced local strategies and crop diversity that help households increase income and food security. These benefits indicate that agroecology is well suited to improve the position of small farms. Key to their achievement has been a production system focused on the women's interests, which include income diversification and family nutrition, as well as friendship and group solidarity. They have also become valued leaders in networks promoting rural women's agency, agroecology, and food sovereignty. This study confirms the importance of prioritizing gender equality in sustainable agriculture initiatives, not only for social justice but also to recognize women's crucial leadership and knowledge for agroecology.